If S1 , S2 , S3 are the sum of n terms of three AP’s, the first term of each being unity and the respective common difference being 1, 2 , 3; prove that 2 . (S1 + S 3 =2S 2(
Answers
Answered by
423
Formula of summation of an A.P:
,
where
= Summation till n terms.
a = First term of sequence
d = Common Difference.
Now, using this formula, we get
S1 =
,
S2 =
, &
S3 =
.
Therefore, to get the desired equation, we add S1 and S3.
∴ S1 + S3 =![\frac{n+n^{2}}{2} + \frac{3n^{2}-n}{2} \frac{n+n^{2}}{2} + \frac{3n^{2}-n}{2}](https://tex.z-dn.net/?f=+%5Cfrac%7Bn%2Bn%5E%7B2%7D%7D%7B2%7D+%2B++%5Cfrac%7B3n%5E%7B2%7D-n%7D%7B2%7D+)
=![\frac{n^{2}+3n^{2}}{2} \frac{n^{2}+3n^{2}}{2}](https://tex.z-dn.net/?f=+%5Cfrac%7Bn%5E%7B2%7D%2B3n%5E%7B2%7D%7D%7B2%7D+)
=![\frac{4n^{2}}{2} \frac{4n^{2}}{2}](https://tex.z-dn.net/?f=+%5Cfrac%7B4n%5E%7B2%7D%7D%7B2%7D+)
=![2n^{2} 2n^{2}](https://tex.z-dn.net/?f=2n%5E%7B2%7D)
= 2(S2).
∴, S1 + S3 = 2(S2).
Hence proved.
where
a = First term of sequence
d = Common Difference.
Now, using this formula, we get
S1 =
S2 =
S3 =
Therefore, to get the desired equation, we add S1 and S3.
∴ S1 + S3 =
=
=
=
= 2(S2).
∴, S1 + S3 = 2(S2).
Hence proved.
Answered by
132
Please see the attachment.
Attachments:
![](https://hi-static.z-dn.net/files/d01/8100818e1536e15ee347c209a612f6bf.jpg)
Similar questions